THE ANALYSIS OF FUTURE PRESCHOOL TEACHERS’ MOTIVES FOR LEARNING A FOREIGN LANGUAGE - Shykyrynska, Oleksandra; Vyshkivska, Vanda; Yatsyshin, Oleg; Malinka, Olena; Lobachuk, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article focuses on the relevance of the study of future preschool teachers’ motivation for learning foreign languages, which is as follows: the ability to formally and informally communicate with foreign colleagues at conferences, seminars, symposia for discussing current issues of preschool education, the search for new text, graphic, audio and video information contained in foreign language materials for professional purposes, the creation of a foreign language educational environment in a preschool institution in order to teach children the elements of a foreign language. A definitive analysis of the concept of “motive” in domestic and foreign scientific sources is carried out. Based on the definition of motives for learning a foreign language by second-year students – future preschool teachers (according to the method of O.Yatsyshin), as well as on the observation of their activities in the process of learning English and during confidential conversations with them, the students’ motives for learning English as a foreign language are analyzed. Psychological and pedagogical conditions of the formation of future preschool teachers’ motives for learning English as a foreign language are presented: organization of cross-cultural communicative activity of students, creation of situations of guaranteed success during the learning process, creation of a professionally oriented educational environment. It is emphasized that the abovementioned conditions should be both interconnected and interdependent; they should also be implemented in the educational process of a higher education institution not gradually, but simultaneously and systematically, in order to receive the sustainable positive motives of future preschool teachers for learning a foreign language.